Pembelajaran Merdeka Belajar dalam Perkembangan Teknologi dalam Perspektif Pembelajaran Daring Program Belajar Merdeka - Hajar, Sitti; Nurwahida; Amin, Saiful; Kaharuddin (Elementary Journal : Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Technological developments have played a significant role in the world of education. The benefits of technology for the world of education include obtaining information, increasing students’ learning abilities, facilitating access to learning, making material more interesting and being able to increase interest in learning. Indonesian is one of the lessons that must keep up with technological developments. Independent Campus is the policy of the Minister of Education and Culture, where the goal and mission is to encourage students to master various knowledge that is useful for entering the world of work. Through this policy, the Merdeka Campus provides opportunities for students to choose the courses they want to take as well as freedom of thought and innovation for lecturers and students. This article will also explain that technological developments and the Merdeka Campus learning program play a very important role in improving the quality of education, one of which is in learning Indonesian. This can be seen from the implementation of the benefits of technology in improving Indonesian language learning and the Merdeka Campus policy which provides freedom to innovate and study independently which is able to increase creativity in learning Indonesian.